Pengaruh Kualitas Jasa Dan Nilai Pelanggan Terhadap Minat Kunjungan Ulang Melalui Kepuasan Pasien Di Poli Umum Di RSISA Semarang - Retno Kusniati; Naili Farida; Sudiro Sudiro (Jurnal Manajemen Kesehatan Indonesia, 2016)
Patient’s satisfaction is one of the indicators in assessing a service quality at a hospital. Fluctuations in number of total visit of patients and declining trend of old patient visit number at a general polyclinic at Sultan Agung Islam Hospital (SAIH) in Semarang during the period of 2010-2013 indicated that there were any problems at the polyclinic. The aim of this study was to comprehensively analyse a service quality and customer value that influenced towards willingness to revisit through patient’s satisfaction at outpatient/general polyclinic at SAIH in Semarang.This was an explanatory study using cross-sectional approach and an analytic method. Population was all patients at outpatient unit/general polyclinic at SAIH in Semarang who had visited the polyclinic at least two times. As many as 125 respondents were selected as samples using a method of purposive sampling. Data were collected using a structured questionnaire and measured using Likert scales of 1-5 and analysed using SEM performed by software of Smart PLS 2.0. The results of this research showed that the service quality and the customer value positively significantly influenced patient’s satisfaction. In addition, the patient’s satisfaction positively significantly influenced willingness to revisit. The patient’s satisfaction could be explained by the service quality and the customer value equal to 45.3%. Meanwhile, willingness to revisit could be explained by the service quality, the customer value, and the patient’s satisfaction equal to 45.0%. Overall, the service quality and the customer value at the general polyclinic of SAIH in Semarang are good. Notwithstanding, there still needs improvement in timeliness of service, availability of accurate service information, consistent and polite officers, greetings, and smiling to patients in order to improve patient’s satisfaction and to increase willingness to revisit at the general polyclinic of SAIH in Semarang.